Análise da viabilidade de produção de madeira-plástica utilizando Poliestireno (PS) e madeiras da Amazônia - (:unkn) unknown (Universidade Federal do Amazonas, 2017)
The growing market demand for products and services causes a large amount of solid waste to be produced. Among the main primary materials are plastic and wood which are considered waste both domestically and industrially. Due to the large amount of plastic and wood waste produced, studies with the purpose of developing a composite material that has properties close to the wood and that has a reinforcement of thermoplastic loads in its matrix are of fundamental importance. In this sense, the present study had as objectives: to define the configurations and compositions of the panels, in relation to the variables adopted in their manufacture; Evaluate the quality of wood-plastic panels with different compositions of wood and plastic; Verify the feasibility of using the panels in the manufacture of artifacts; And evaluate the amount of waste generated to meet market demand. As plastic matrix was used industrial waste polystyrene, in different granulometries and sawdust of different species of tropical Amazonian trees. The residues were mixed in different proportions from 50% plastic to 100%. After pressing and subsequent cooling, the panels were evaluated for density, swelling in thickness, water absorption dynamic modulus of elasticity with Stress Wave Timer, parallel compression and static bending. The workability of the panels was also evaluated for ease of cutting in the saw, drilling by drill, nail and screw in addition to finishing with varnish and carnauba wax. The panels had medium to high density. The results of swelling and absorption were better when compared to works made with particle panels. In the mechanical tests the best results were with panels that had lower polystyrene granulometry and, depending on the granulometry, with a higher proportion of plastic. It is possible to produce wood-plastic panels cheaply, reusing wood and plastic waste from large industries by the thermopressing method.
Keywords: Termoprensagem; Resíduos sólidos; Madeira-plástica; CIÊNCIAS AGRÁRIAS: RECURSOS FLORESTAIS E ENGENHARIA FLORESTAL